2003
DOI: 10.1159/000070133
|View full text |Cite
|
Sign up to set email alerts
|

Management and Follow-Up of Impacted Ureteral Stones

Abstract: Introduction: Impacted stones are those that remain unchanged in the same location for at least 2 months. Materials and Methods: We evaluated 42 patients with impacted ureteral stones, and followed them for two and a half years to check for long-term results. The calculi location included all three segments of the ureter (proximal, mid and distal). Patients’ age ranged from 22 to 83 years (mean 52.5 years). Primarily, patients were manipulated with extracorporeal shock wave lithotripsy (ESWL) in situ, or follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…In the same series, spontaneous passage rate was also dependent on stone location (48% for stones in the proximal ureter, 60% for mid ureteral stones, 75% for distal stones, and 79% for ureterovesical junction stones). In addition to size and location, there are also other interfering factors such as obesity, level of renal obstruction and type of medical therapy (16). In our study, most of the stones and fragments that passed spontaneously were 7 mm or less and located in the lower ureter.…”
Section: Co��entsmentioning
confidence: 55%
“…In the same series, spontaneous passage rate was also dependent on stone location (48% for stones in the proximal ureter, 60% for mid ureteral stones, 75% for distal stones, and 79% for ureterovesical junction stones). In addition to size and location, there are also other interfering factors such as obesity, level of renal obstruction and type of medical therapy (16). In our study, most of the stones and fragments that passed spontaneously were 7 mm or less and located in the lower ureter.…”
Section: Co��entsmentioning
confidence: 55%
“…Seven patients were excluded for several reasons, while 80 were included in the study. Inclusion criteria were patients with an impacted stone \20 mm located in the same position on two consecutive KUB for at least 1 month, nonvisualization of contrast medium beyond the stone on intravenous urography (IVU) or per-operative retrograde ureterography, and failure to pass guide wire by the side of the stone [1,2]. Exclusion criteria were patients on permanent anticoagulants, those with ureteral strictures, multiple stones, anatomical abnormalities, renal insufficiency, and a previously unsuccessful URS procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Impacted stones are defined as calculi that have remained in the same position for at least 2 months [1], failure to pass a guide wire by the side of the stone, failure to visualize contrast medium beyond the stone [2]. Extracorporeal shockwave lithotripsy (SWL) is a non-invasive modality but the stone-free rate falls dramatically for impacted calculi [3,4] because of lack of natural expansion space around the stone [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…impacted ureteral calculi constituted a clinical controversy for the practising urologists and the objective assessment of impaction for a well planned treatment of such stones is stil a matter of discussion [2,11,12]. Accumulated literature data have well demonstrated that the as the stone gets buried into the ureteric wall, this condition (often being called as "impaction") may affect not only the spontaneous passage rates; but also the ultimate success as well as procedure related complications of endourological stone removal methods [1,[12][13][14][15][16].…”
Section: Assessment Of Ureteral Stone Impaction Into the Ureteric Wallmentioning
confidence: 99%